BENTUK MEDIA EDUKASI PERILAKU SEKSUAL BERISIKO UNTUK REMAJA TINGKAT SEKOLAH MENRENGAH PERTAMA DI KABUPATEN BADUNG PROPINSI BALI - Moh. Fairuz Abadi (Stikes Wira Medika Bali, 2017)
Health promotion is a process to build self awareness to avoid of the health risk. Education about sexual risk behavior for teenagers is one of them. Education media had a function to communicate and spread the information of health. The education media on sexual risk behavior for teenagers was a important thing for health promotion programe. The research pupouse are to expose and describes the form of education media on sexual risk behavior for teenagers at junior high schools in Badung Regions by using qualitaive method. The respondens are choice by purposive. The result shown that there is many form of education media for sexual risk behavior for teenagers, wich are booklet, power poin slide, leaflet/brocure, social media, video, TV,book and peer. Media that was ever used are booklet, power poin slide, leaflet/brocure, social media and article. Media that was more used are social media, leaflet/brocure and power poin. There is no information about the effectivity level of media. The outcame of education media for sexual risk behavior only increase cognitive aspect. Based from all of respondens speaks, media which is suitable are slide/power poin, leaflet/brocure, sosial media dan video.